MANAGEMENT OF DIABETES MELLITUS (TYPE 2) WITH ANTI DIABETIC AYURVEDIC MEDICINE – A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2019)
Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar level (hyperglycaemia) with or without some classical features- polyuria, polydipsia, polyphagia, burning sensation etc. In Ayurveda diabetes comes under Prameha, is one of the ‘Ashtau Mahagadas’. It is a Vatik subtype of Prameha called Madhumeha. Some Madhumehahar (Anti-diabetic) Ayurvedic herbal medicines are very much effective for managing the day to day diabetic life. The present article deals with a newly diagnosed case of Type 2 DM since 3 Days. Still he was not taking any allopathy medicine. By analyzing the concept of pathogenesis of this patient it was understood that Kapha- Pittavrit -Vata Dosha is the chief vitiating factor and other factors like manifestation Meda, Kleda, Vasa, Ambu and Ojas with Dhatwagni Mandya are the co-factor for it. By considering the Nidana, Dosha and Dusya (factors and co-factor), a judicial combination of Ayurveda drugs- Jamun- Gudmar- Nagarmotha Sudarshan- Giloy- Nagkeshar- Arjun Churna was advised to take orally in morning and evening with luke warm water. At the time of consultation his FBS and PPBS was too high i.e., FBS- 366 and PPBS – 614. After taking the prescribed formulation for 3 months his sugar level came down to normal range. Now patient is under supervision of OPD AIIA at fort night interval. The prescribed combination of drugs showed better response in Type 2 DM. Assessment using major Ayurveda parameters for evaluating Roga, Agni, Deha and Chetas, Bala came down to the normal level.